1983
DOI: 10.1021/jo00156a045
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous polar aprotic solvents. Efficient sources of nucleophilic oxygen

Abstract: The replacement of various functional groups with oxygenated moieties is of considerable importance in synthetic endeavors and has led, over the years, to the development of several reagents that serve as nucleophilic sources of oxygen, including hydroxide,1 peracids,2 su-(1) See:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(30 citation statements)
references
References 2 publications
2
27
0
1
Order By: Relevance
“…The isolation of pure products was carried out via thin layer chromatography (silica gel 60 GF 254 , Merck). Except for 1-hydroxyhexan-2-one (2l), which was prepared by selective oxidation of diols [29], all a-hydroxyketones were synthesized by direct a-hydroxylation of ketones with [bis(trifluoroacetoxy)iodo]benzene and trifluoroacetic acid [30] as well as a-bromination of of ketones followed by hydroxylation [31,32]. Commercially available organic and inorganic compounds were used without further purification.…”
mentioning
confidence: 99%
“…The isolation of pure products was carried out via thin layer chromatography (silica gel 60 GF 254 , Merck). Except for 1-hydroxyhexan-2-one (2l), which was prepared by selective oxidation of diols [29], all a-hydroxyketones were synthesized by direct a-hydroxylation of ketones with [bis(trifluoroacetoxy)iodo]benzene and trifluoroacetic acid [30] as well as a-bromination of of ketones followed by hydroxylation [31,32]. Commercially available organic and inorganic compounds were used without further purification.…”
mentioning
confidence: 99%
“…25,26 Hutchins and Taffer reported 27 the substitution of short chain alkyl halides by KOH/H 2 O to alcohols in the presence of polar aprotic solvents such as dimethyl sulfoxide, hexamethylphosphoramide, or N-methylpyrrolidone. However, the reaction often gave undesired elimination products, because the KOH/H 2 O acted as a strong base.…”
Section: Resultsmentioning
confidence: 99%
“…tertiary, benzyl and allyl halides, can be hydrolysed easily by water in various solvents 18 or by aqueous bicarbonate 19 . However, the hydrolysis of primary alkyl halides is more difficult and has usually been achieved using alkali metal hydroxides 18 , though in a few simple cases it has been shown that water in N-methylpyrrolidone or hexamethylphosphoramide can achieve hydrolysis 20 . Primary bromides and iodides have also been hydrolysed using bis(tributyltin) oxide in the presence of silver salts 21 , however, the 4H-pyran-4-one ring is unstable under basic conditions, therefore, direct substitution of halide by a hydroxyl group is not possible.…”
Section: Resultsmentioning
confidence: 99%